Maximixing Consumer Loyalty Based Website Design Quality, Electronic Word Of The Mouth And Trust As Medition - Humairoh Humairoh; Mohammad Annas (Cita Konsultindo Research Center, 2023)
This looks at pursuits to determine the effect of the quality of website design and electronic word of mouth on consumer loyalty thru trust as a mediating variable. This kind of study is quantitative studies. The sample on this look amounted to 96 respondents using a probability sampling method for the people of Tangerang City who had shopped at the e-commerce Shopee. Data was taken using a questionnaire instrument with a Likert scale score of 1-5.The effects of the examination display that there may be a positive and significant impact on the quality of website design on trust. The quality of website design on consumer loyalty and trust is a mediating variable between the great of website design on customer loyalty. This study additionally suggests that electronic word of mouth has a positive and significant impact on trust, electronic word of mouth has a positive and significant effect on consumer loyalty, and trust is a mediating variable between the electronic word of mouth on consumer loyalty. The following determination of 0.659 patron loyalty may be defined through the quality of website design, electronic word of mouth, and accepted as accurate with 65.9%. The rest, with the aid of other variables now not examined. The recommendations that Shopee can convey further growth consumer self-assurance on the way to grow customer loyalty so that customers do not switch to the competition.